How speculative designs produce new potentials for education research in digital culture. Issue 5 (2nd September 2020) - Ehret, Christian; Čiklovan, Luka
ABSTRACT: This article reports on a speculative design experiment, wherein the authors produced a critical remix video as intervention into the spread of toxic technocultural discourse on Twitch.tv (Twitch), an online platform in which content creators stream live content alongside a live chat audience. It focuses on the authors' development of a speculative design process for education research in the context of livestreaming technoculture. This process began with a multimodal discourse analysis showing how specific discourse processes – amplification, waving, and network influencing – on a popular Twitch stream produced agonistic conflict and sometimes toxic discourse stemming therefrom. These findings from the multimodal discourse analysis informed a speculative intervention performed through the production of a critical remix video, which recontextualized the same discourse processes, thereby producing a working critique of potentially toxic agonism on this Twitch channel. The article also illustrates how speculative design experiments in digital culture may help develop new pedagogic potentials that catalyze social change through youths' expanded and nuanced repertoire of digital practices in the future.